Iron sand briquette and method preparing the same
Patent Information
- Application Number
- TW114108874
- Authority / Receiving Office
- TW · TW
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-03-11
- Publication Date
- 2026-09-16
- Estimated Expiration
- 2045-03-10
AI Technical Summary
Conventional methods for using iron ore in steelmaking are inefficient, costly, and produce high carbon emissions, while existing slag recycling technologies using sodium silicate or cement binders are not suitable for high-temperature blast furnace processes due to sodium content or degradation issues.
Manufacturing iron sand blocks with a composition containing over 70 wt% iron, 3 to 12 wt% aluminum binder, and 4 to 8 wt% water, which are agglomerated and cured to form blocks with high metallic iron content and suitable strength for use as furnace charge.
The iron sand blocks achieve effective carbon reduction, reduce carbon emissions, and meet high-temperature and room-temperature strength requirements, enabling their use in converters, electric furnaces, and blast furnaces.
Abstract
Description
Iron sand blocks and their manufacturing methods This disclosure relates to an iron sand block and a method for manufacturing the same, and more particularly to an iron sand block used as furnace charge and a method for manufacturing the same. In the ironmaking process of conventional steel mills, iron ore is a commonly used raw material, whose main component is ferric oxide (Fe2O3). 2O 3) With iron(III) oxide (Fe) 3O 4) Iron oxides. The ironmaking process uses a large amount of carbon-containing reducing agent to reduce iron oxides in iron ore to metallic iron, and produces a large amount of carbon dioxide greenhouse gas. In order to achieve the goal of carbon reduction, the amount of carbon reducing agent used can be reduced and / or the iron-containing substances in the ironmaking slag can be recycled and reused. The conventional method for reducing carbon reducing agent is to replace iron ore with high-iron content iron granules or hot briquetted iron (HBI). However, the production of iron granules is lower than the estimated usage, and HBI is expensive, which is not conducive to reducing production costs. Furthermore, conventional slag recycling technologies use sodium silicate, pregelatinized starch, cement, or organic materials as binders to process iron sand or iron powder with low iron content into briquettes. However, iron sand or iron powder cannot effectively reduce carbon due to its low iron content. Moreover, the high sodium content of sodium silicate binder has an adverse effect on the blast furnace. Briquettes containing cement binders and organic binders do not have high-temperature strength greater than 500°C and cannot be used in blast furnace ironmaking processes. In view of this, there is an urgent need in the field for an iron sand block that can be used as furnace charge and a method for manufacturing it. To overcome the above problems, this disclosure provides an iron sand block formed from a composition containing iron sand. The iron sand contains more than 70 wt% iron by total weight, and the composition further contains 3 to 12 wt% aluminum binder and 4 to 8 wt% water. This disclosure also provides a method for manufacturing iron sand blocks, comprising: mixing components to form a mixture; blistering the mixture to form a block; and allowing the block to stand to form iron sand blocks. In at least one embodiment of this disclosure, iron sand blocks with a high metallic iron content and suitable room temperature and high temperature strength can be used as furnace charge to achieve the goal of effective carbon reduction, thereby enabling its widespread application in converters, electric furnaces and / or blast furnaces. The following embodiments are provided to illustrate this disclosure in detail. Those skilled in the art will readily understand the advantages and effects of this disclosure upon reading it, and it can also be implemented or applied in other different embodiments. Therefore, the following embodiments for carrying out this disclosure can be modified and / or changed without departing from its different aspects and scope of application, and any element or method within the scope of this disclosure can be combined with any other element or method disclosed in any embodiment of this disclosure. As used herein, the articles “a,” “one,” “the,” and “the” refer to one or more (i.e., at least one) grammatical object of the article, unless otherwise clearly stated, and “or,” “ / ,” and “and / or” are used interchangeably, unless otherwise clearly stated. As used herein, the phrase "at least one" refers to one or more elements and should be understood to mean at least one element selected from any one or more of the listed elements, but not necessarily including at least one of each of the listed elements, and does not exclude any combination of elements in the listed elements. This definition also allows elements to be present as needed, other than those identified in the list of elements referred to by the phrase "at least one," whether related to or unrelated to those identified elements. Thus, as a non-limiting example, "at least one of A and B" (or, equivalently, "at least one of A or B", or, equivalently, "at least one of A and / or B") in one embodiment may refer to at least one A, including more than one A as needed, with no B (and including elements other than B as needed); in another embodiment, it is at least one B, including more than one B as needed, with no A (and including elements other than A as needed); in yet another embodiment, it is at least one A, including more than one A as needed, and at least one B, may include more than one B as needed (and may include other elements as needed). As used herein, the terms "comprising," "including," "containing," "having," and any other variations thereof are intended to cover non-exclusive inclusions. For example, when describing something as "comprising" a limitation, it may additionally include other components, elements, parts, structures, regions, portions, devices, systems, steps, or connections, unless otherwise stated, and should not exclude other limitations. The numerical ranges used herein are inclusive and composable. Any value falling within these ranges can be considered a maximum or minimum value from which subranges can be derived. For example, the numerical range "3 to 12 wt%" includes any subrange between the minimum value of 3 wt% and the maximum value of 12 wt%, such as subranges from 3 to 6 wt%, 4 to 12 wt%, 3.5 to 10 wt%, etc. Furthermore, multiple values used herein can be selected as maximum and minimum values as needed to derive numerical ranges. For example, numerical ranges of 3 to 7 wt%, 3 to 12 wt%, and 7 to 12 wt% can be derived from values of 3 wt%, 7 wt%, and 12 wt%. The term "about" as used in this disclosure refers to a typical tolerance range within the relevant technical field. For example, "about" can be understood as approximately two standard deviations from the mean. When "about" appears before a series of numbers or ranges, it should be understood that "about" may modify each number in that series or range. For example, numerical values are intended to cover variations of ±20%, ±10%, ±5%, ±1%, ±0.5%, or ±0.1% from the numerical values. As used herein, numerical ranges are inclusive and composable, and any numerical value falling within the numerical ranges herein can be considered a maximum or minimum value from which subranges are derived. For example, it should be understood that the numerical range "22 to 36%" includes any subrange between the minimum value of 22% and the maximum value of 36%, such as subranges from 22.5% to 35%, from 23% to 34%, and from 24% to 33%. Such variations in numerical values may occur due to, for example, experimental errors, typical errors in the measurement or processing of the manufacturing composition, the source of the starting materials or components used in this disclosure, differences in manufacturing or purity, or similar considerations. Alternatively, the term "about" means within an acceptable average standard deviation when considered by someone of ordinary skill in the art. Unless otherwise expressly stated, all ranges, quantities, values, and percentages disclosed herein, such as the amount of material, duration of time periods, temperature, operating conditions, ratios of quantities, etc., should be understood to be modified by the term "about" in all cases. In at least one embodiment of this disclosure, a blast furnace byproduct, namely reduced iron sand made from slag, is used. This reduced iron sand has a particle size of less than about 8 mm and a metallic iron content of more than about 70 wt%, with an annual production of about 100,000 tons. In some embodiments, desulfurization slag produced from the hot metal desulfurization process is used, which, after crushing, screening, and magnetic separation, can produce desulfurized iron sand. Generally, furnace charge needs to be transported over long distances for return to the blast furnace, therefore, the furnace charge must have specific room temperature crushing strength to prevent breakage during transportation. In addition, the furnace charge needs to undergo a 550°C reduction disintegration index (RDI) test, similar to sintered ore, to determine that the furnace charge has a high-temperature strength with an RDI of less than or equal to 38%, to prevent the furnace charge from disintegrating in the upper part of the blast furnace when it is fed into the blast furnace, resulting in poor blast furnace permeability. Because the particle size of reduced iron sand is relatively fine, it must be processed into agglomerates by high-pressure molding, then cured for a specific time, and only after passing the furnace charge acceptance standards can it be used as furnace charge. Therefore, this disclosure uses the RDI test to determine whether the iron shot meets the high-temperature strength requirement of RDI less than or equal to 38%, and uses commercially available instruments to determine whether the iron shot has a strength greater than 70 kg / cm². 2 The room temperature crushing strength was used to assess whether iron sand blocks could be used in blast furnace ironmaking processes. The term "550℃ RDI test" in this disclosure refers to a reducing atmosphere (10.5 l / min N2) at 550±5℃. 500 g of iron sand sample was reduced with CO at a rate of 2 and 4.5 l / min for 30 min. The sample was then cooled and placed in a rotating drum (130 mm inner diameter × 200 mm length). The drum was rotated 900 times at a speed of 30 rpm. The sample was then sieved through a 2.8 mm mesh screen. The RDI was calculated using the following formula: RDI = (weight of sample smaller than 2.8 mm after sieving / weight of sample before rotation) × 100%. The term "curing" in this disclosure refers to a material that has been left to stand in a well-ventilated environment at normal temperature, normal pressure, and normal humidity. In this specification, normal temperature means approximately 15 to 25°C, normal pressure means approximately 0.95 to 1.05 atm, and normal humidity means approximately 60 to 80%. The term "iron pellets" disclosed herein refers to iron-containing materials with a particle size of approximately 8 mm to 5 cm. Generally speaking, iron pellets, due to their coarse particle size, can be used as furnace feed without the need for agglomeration. The term "iron sand" disclosed herein refers to iron-containing materials with a particle size of less than about 8 mm. Generally speaking, iron sand, due to its fine particle size, must be agglomerated before it can be used as furnace charge. The term "CSH cementing phase" in this disclosure refers to the solid phase structure of hydrated calcium silicate (CSH) cement in cement paste. In at least one embodiment of this disclosure, the composition may contain iron shot. In at least one embodiment of this disclosure, the iron content, based on the total weight of the iron shot, may be greater than about 70 wt%, for example, but not limited to: about 70 to 90 wt%, about 71 to 89 wt%, or about 72 to 88 wt%. In some embodiments, the iron content may be about 70, 71, 72, 73, 74, 75, 76, 77, 78, 79, 80, 81, 82, 83, 84, 85, 86, 87, 88, 89, or 90 wt%, but this disclosure is not limited thereto. In at least one embodiment of this disclosure, the content of the aluminum binder, based on the total weight of the iron shot, may be about 3 to 12 wt%, for example, but not limited to: about 3.5 to 11.5 wt%, about 4 to 11 wt%, or about 4.5 to 10.5 wt%. In some embodiments, the content of the aluminum binder may be about 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, 9, 9.5, 10, 10.5, 11, 11.5, or 12 wt%, but this disclosure is not limited thereto. In at least one embodiment of this disclosure, the composition may contain a specific amount of water. In at least one embodiment of this disclosure, the water content, based on the total weight of the iron shot, may be about 4 to 8 wt%, for example, but not limited to: about 4.2 to 7.8 wt%, about 4.4 to 7.6 wt%, or about 4.6 to 7.4 wt%. In some embodiments, the water content may be about 4, 4.2, 4.4, 4.6, 4.8, 5, 5.2, 5.4, 5.6, 5.8, 6, 6.2, 6.4, 6.6, 6.8, 7, 7.2, 7.4, 7.6, 7.8, or 8 wt%, but this disclosure is not limited thereto. In some embodiments, when the water content is less than 4 wt%, the aluminum binder cannot effectively hydrate and exert a bonding effect. In some embodiments, when the water content is greater than 8 wt%, it leads to molding difficulties. In at least one embodiment of this disclosure, the particle size of the iron shot may be less than about 8 mm, for example, but not limited to: about 0.5 to 8 mm, about 1 to 7.5 mm, or about 1.5 to 7 mm. In some embodiments, the particle size of the iron shot may be about 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, or 8 mm, but this disclosure is not limited thereto. In some preferred embodiments, the particle size of the iron shot is less than about 5 mm. In at least one embodiment of this disclosure, the iron sand may be reduced iron sand. In at least one embodiment of this disclosure, the iron sand may be desulfurized iron sand. In at least one embodiment of this disclosure, the aluminum binder may be an aluminum refractory (also known as a high-alumina refractory), preferably an aluminosilicate or aluminosilicate refractory, and more preferably an aluminosilicate refractory. Aluminosilicate refractory has advantages as a binder due to its fluidity, cost advantage, and good availability. In some embodiments, the aluminosilicate refractory may include, by weight, more than about 40 wt% aluminum oxide (Al₂O₃). 2O 3) More than about 30 wt% of calcium aluminum silicate hydrate (Ca₃Al₂(SiO₄)₃-x(OH)₄x), where x is 1.5 to 3, and less than about 20 wt% of ferric oxide (Fe₂O₃). 2O 3), and less than about 0.5 wt% potassium oxide (K 2O) and sodium oxide (Na) 2O). The sodium content of the aluminosilicate refractory binder is much lower than that of the sodium silicate in the conventional sodium silicate binder, making it more suitable for preparing iron sand blocks for use in blast furnaces. In at least one embodiment of this disclosure, the aluminum binder may not include a sodium compound. In some embodiments, the sodium compound may be sodium carbonate (Na₂SO₄). 2CO 3) Sodium bicarbonate (NaHCO3) 3) Sodium hydroxide (NaOH), sodium nitrate (NaNO3) 3) Sodium phosphate (Na) 3PO 4) Sodium thiosulfate (Na) 2S 2O 3.5H 2O), sodium fluoride (NaF), sodium chloride (NaCl), sodium acetate (CH2O), sodium fluoride (NaF), sodium chloride (NaCl), sodium acetate (CH2O) 3COONa) or sodium silicate (Na) 2SiO 3), but this disclosure is not limited thereto. In a preferred embodiment, the sodium compound is sodium silicate. In at least one embodiment of this disclosure, the iron sand block may have a density greater than about 70 kg / cm³. 2 The room temperature crushing strength, for example, but not limited to: approximately 70 to 300 kg / cm² 2 Approximately 80 to 290 kg / cm² 2 Or approximately 90 to 280 kg / cm 2 In some embodiments, the room temperature crushing strength may be approximately 70, 80, 90, 100, 110, 120, 130, 140, 150, 160, 170, 180, 190, 200, 210, 220, 230, 240, 250, 260, 270, 280, 290, or 300 kg / cm². 2 However, this disclosure is not limited to this. In at least one embodiment of this disclosure, the iron shot block may have a reduction pulverization index (RDI) of less than or equal to 38%, for example, but not limited to: about 18 to 38%, about 19 to 37%, or about 20 to 36%. In some embodiments, the room temperature crushing strength may be about 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, or 38%, but this disclosure is not limited thereto. This disclosure enables the produced iron shot block to have an RDI of less than or equal to 38% by including an aluminum binder in the composition. In at least one embodiment of this disclosure, the method for manufacturing iron sand blocks may include mixing components, preferably mixing components at room temperature. In at least one embodiment of this disclosure, the method for manufacturing iron shot blocks may include a block-forming mixture, preferably by placing the mixture in a steel mold at a concentration of 220 to 1200 kg / cm³. 2 Pressure-formed block mixture. In at least one embodiment of this disclosure, the pressure of the briquetting mixture (i.e., the briquetting pressure) may be, but is not limited to, about 220 to 1175 kg / cm³. 2 Approximately 230 to 1150 kg / cm² 2 Or approximately 240 to 1125 kg / cm² 2 In some embodiments, the block forming pressure may be approximately 220, 230, 240, 250, 300, 350, 400, 450, 500, 550, 600, 650, 700, 750, 800, 850, 900, 950, 1000, 1050, 1100, 1125, 1150, 1175, or 1200 kg / cm³. 2 However, this disclosure is not limited to this. In at least one embodiment of this disclosure, the method for manufacturing iron sand blocks may include mixing a block for 1 to 5 seconds. In at least one embodiment of this disclosure, the method for manufacturing iron sand blocks may include allowing the block to stand, preferably allowing the block to stand in a ventilated environment at room temperature for 5 to 10 days. Since the iron sand disclosed herein contains more than 70 wt% iron, its use as furnace charge can reduce the amount of carbon reducing agent required, thereby reducing carbon emissions and achieving the goal of effective carbon reduction. Furthermore, this disclosure uses an aluminum binder to manufacture iron sand blocks with excellent high-temperature strength and room-temperature crushing strength, which can be widely used in converters, electric furnaces, and / or blast furnaces. Example Examples 1 to 3 Based on empirical judgment, provide any amount of iron sand. Thoroughly mix the iron sand, aluminum binder, and water at room temperature to obtain a mixture. Add the mixture to a steel mold with a diameter of approximately 4 cm and a height greater than 2 cm at room temperature, then apply molding pressure to obtain cylindrical blocks with a diameter of approximately 4 cm and a height of approximately 2 cm. Allow the blocks to cure for 7 days to obtain the iron sand blocks of Examples 1 to 3. The particle size, iron content, binder dosage, water dosage, and agglomeration pressure of the iron sand from Examples 1 to 3 are recorded in Table 1 below. Furthermore, the room temperature crushing strength and RDI of the iron sand blocks from Examples 1 to 3 are measured and recorded in Table 1 below. [Table 1] Referring to Table 1, the iron content of the iron sand in Examples 1 to 3 is approximately 75 to 90 wt%. Using the agglomerated product as furnace charge in a blast furnace can reduce the amount of carbon reducing agent required, enabling the ironmaking process to effectively reduce carbon emissions, while also promoting the resource utilization of iron-containing by-products in integrated steel mills. Furthermore, as shown in Table 1, the room temperature crushing strength of the iron sand blocks in Examples 1 to 3 is as high as 150 to 250 kg / cm². 2 Much greater than 70 kg / cm 2 Therefore, it can prevent the iron sand blocks from breaking during transportation. It should be understood that conventional slag recycling technologies typically use sodium silicate or cement as binders. However, the high sodium content of sodium silicate can have adverse effects on blast furnaces, while the CSH binder phase of cement will degrade at 500 to 700°C, causing its agglomerates to lose high-temperature strength and thus lack suitable RDI. In contrast, Examples 1 to 3 use alumina refractory cement as a binder, which not only avoids adverse effects on the blast furnace but also provides agglomeration and bonding properties, enabling the produced iron sand blocks to achieve an RDI of approximately 22% to 36%. Passing the 550°C RDI test, it meets the requirement of an RDI less than or equal to 38%. Therefore, the iron sand blocks disclosed herein can indeed achieve the technical effect of having high-temperature strength and being applicable to blast furnace ironmaking processes, overcoming the predicament of conventional agglomerates being unresistant to high temperatures and having an RDI that cannot meet the requirements of blast furnace feed. The above descriptions are merely some embodiments of this disclosure. Those skilled in the art will easily understand that various modifications and alterations can be made to each embodiment without departing from the teachings of this disclosure. Therefore, all equivalent changes and modifications made within the scope of the claims of this disclosure should be considered within the scope of this disclosure. none. none. none. none.
Claims
1. An iron shot block, formed from a composition comprising: Iron sand, comprising: more than 70 wt% iron by weight of the total iron sand; 3 to 12 wt% aluminum binder by weight of the total iron sand; and 4 to 8 wt% water by weight of the total iron sand. The iron sand block as described in claim 1, wherein, The iron sand has a particle size of less than 8 mm. The iron sand block as described in claim 1, wherein, This iron sand is reduced iron sand. The iron sand block as described in claim 1, wherein, The iron sand is desulfurized iron sand. The iron sand block as described in claim 1, wherein, This aluminum binder is an aluminum refractory material. The iron sand block as described in claim 1, wherein, The aluminum binder is an aluminum-silica refractory or an aluminum-magnesium refractory. The iron sand block as described in claim 1, wherein, The aluminum binder is an aluminum-silica refractory material. The iron sand block as described in claim 1 has a strength greater than 70 kg / cm³. 2 Crushing strength at room temperature. The iron sand block as described in claim 1 has a reduction pulverization index of less than or equal to 38%. A method for manufacturing an iron shot block as described in any one of claims 1 to 9, comprising: Mix the components to form a mixture; The mixture is lumped together to form lumps; The material is left to stand to form the iron sand block. As described in claim 10, the mixing of the composition is carried out at room temperature. The method described in claim 10, wherein the blistering of the mixture comprises: The mixture was placed in a steel mold at a pressure of 220 to 1200 kg / cm³. 2 The pressure causes the mixture to clump together. As described in claim 10, the block is left to stand for 5 to 10 days.
